Speech Recognition to Aid Hanyu Pinyin Pronunciation as Part of Mandarin Language Education - Henry Henry; Eryc Eryc (Universitas Internasional Batam, 2024)
International language skills are increasingly more relevant in the globalization era. One of these international languages is Mandarin. Speech Recognition can be used to recognize speech to design an application to train mandarin pronunciation skills.This research examines the design and evaluation of an application that uses speech recognition to assist mandarin language students. Waterfall-type SDLC method is used during the development of the application. Testing is done using a black-box testing method. Questionnaire data of 33 users are collected to assess the application. Results showed